Seam Busters : A Novella - Hood, Mary (Book collections on Project MUSE., 2015)
"Mary Hood's novella Seam Busters explores the connections we make to one another, from the simplest of acts to those moments that define life and death. When Irene Morgan returns to Frazier Fabrics, a family-owned cotton mill in the hardscrabble heart of Ready, Georgia, she joins an eclectic group of women workers sharing their interwoven lives inside and outside the factory. Under constant surveillance and beholden to production quotas and endless protocols presented under the auspices of "American Pride," the women sew state-of-the-art camouflage for U.S. troops fighting in Afghanistan, one of whom is Irene's son. As Irene toils under the stress of the learning curve and production goals in her first ninety days, she comes to embrace the camaraderie of her peers, some of whom play on the mill's bowling team, the Seam Busters. She comes to know Coquita, a shaky veteran returned from three tours in the Middle East; Kit, an angel-haired rule breaker unlucky in love; the stoic Hmong woman Sue Nag; the beaten but not yet defeated K'shaundra; and Jacky, a well-intentioned fool determined to be heard. In time Irene comes to value her bonds with this motley crew as much as with her husband, Deke, on their small farm and with her far-flung children and grandchildren. When the shadow of death travels from the war front to the home front, Hood deftly braids the threads of these disparate lives and stories into a lifeline for Irene, as her entire community gathers together in an impassioned act of mourning ultimately giving rise to mercy"--